On GE-algebras - Bandaru, Ravikumar; Saeid, Arsham Borumand; Jun, Young Bae (Bulletin of the Section of Logic, 2020)
Hilbert algebras are important tools for certain investigations in intuitionistic logic and other non-classical logic and as a generalization of Hilbert algebra a new algebraic structure, called a GE-algebra (generalized exchange algebra), is introduced and studied its properties. We consider filters, upper sets and congruence kernels in a GE-algebra. We also characterize congruence kernels of transitive GE-algebras.